Zinc-based materials for treating dental caries
By using compositions that lead to Zn3(PO)4 and/or (NH4)ZnPO4 deposits or zinc-containing substances containing fluorides, such as [Zn(NH3)4]F2, the problem of SDF causing tooth stains is solved, achieving no The effect of caries treatment that color, antibacterial and promotes remineralization.
Patent Information
- Application Number
- CN202380050735.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-06
- Filing Date
- 2023-04-27
- Publication Date
- 2025-02-18
AI Technical Summary
In existing dental caries treatment methods, silver ammonia fluoride (SDF) causes dark stains on the surface of the teeth, affecting aesthetics and patient acceptance. At the same time, its alternatives such as SDF/KI also have problems such as reduced bond strength and high cost.
Inorganic zinc compounds are formed by diluting the Zn2+/NH3 solution into water using compositions or fluoride-containing zinc substances such as [Zn(NH3)4]F2. (such as ZnO, Zn(OH)2 or Zn(OH)F) is deposited on the surface of caries to replace traditional SDF treatment.
Colorless and stain-free caries treatment is achieved, providing antibacterial activity and a chemical barrier to prevent bacterial invasion, while promoting remineralization of dentin, avoiding aesthetic problems in traditional methods.
Smart Images

Figure BDA0005215566500000141 
Figure BDA0005215566500000181 
Figure BDA0005215566500000191
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Applications No. 63 / 335,634, No. 63 / 479,982, and No. 63 / 483,493, filed on April 27, 2022, January 13, 2023, and February 6, 2023, respectively, the disclosures of which are incorporated herein by reference. Background Art
[0003] Dental caries is traditionally treated by surgical removal of infected tissue, where the biomineral hydroxyapatite (HAp) (Ca 10 (PO4)6(OH)2) has been attacked by acids produced by cariogenic bacteria (mainly acid-producing and acid-resistant bacteria) in the oral cavity. The resulting treatment is then restored with various materials. For early carious lesions, surgical methods have been increasingly replaced by minimally invasive dental (MID) options to halt the progression of damage and promote remineralization to restore damaged but structurally intact dentin.
[0004] Silver diamine fluoride (SDF) has been used in MID to treat early caries. However, a serious disadvantage of the SDF modality is that it produces very deep dark stains, which is problematic for aesthetics and patient acceptance. It is generally believed that SDF reacts with exposed dentin to form silver phosphate (Ag3(PO4)), a semiconductor that undergoes self-reduction upon exposure to visible light. The result is the formation of neutral silver atoms, which assemble into silver nanoparticles. These nanoparticles inherently absorb violet (yellow colloidal phase), but subsequently form aggregates that absorb broadly across the visible spectrum and thus appear black. Although the time course for the formation of black deposits is variable, it occurs as long as SDF is used in water at the clinically recommended concentration of 38% (w / w). The purpose of MID would be well served by a topical agent that is well accepted by parents of pediatric patients, a population that could be the primary beneficiaries of SDF treatment. Unfortunately, parents are reluctant to undergo treatment due to stain formation, especially on anterior teeth.
[0005] To address the stain problem, many chemical agents have been tested, such as ammonium hexafluorosilicate, zinc fluoride, and potassium iodide. Application of SDF followed immediately by a saturated aqueous solution of KI has been recommended for clinical use. However, SDF / KI precipitates have been reported to significantly reduce the bond strength of glass ionomer and composite restorations. Furthermore, even after treatment with SDF / KI, teeth have been reported to discolor over a 14-day period. The cost of the SDF / KI treatment regimen is 15 times higher than the SDF unit dose regimen. Most importantly, KI is contraindicated during pregnancy due to its association with congenital iodide goiter. Many considerations associated with SDF point to the need for alternatives.
[0006] ZnO has been shown to be effective against Streptococcus mutans. Studies have shown that ZnO is converted into zinc phosphate in saliva, which then acts as Zn 2+ reservoir, inhibiting bacterial proliferation and caries progression.
[0007] Water-dispersible ZnO has been described. The delivery of high concentrations of antimicrobial agents is beneficial for the formation of a chemical barrier that prevents bacterial invasion and proliferation. However, the retention of ZnO aqueous dispersions in carious tissue is challenging due to the lack of an obvious pathway to convert the ZnO dispersion into a mechanically stable mineral phase.
[0008] There are several routes to obtain the desired mineral. ZnO nanoparticles have been reported. 2+ Preparation of 1.25 M ethanol-rich solution of ZnO nanoparticles has been reported by using triethanolamine as a capping agent. It has also been shown that the nanoparticles easily aggregate in electrolyte-containing solutions, which is essential for the deposition of ZnO in dentinal tubules. Once deposited, the low-solubility nanoparticles are expected to dissolve slowly, with the conversion of ZnO to phosphite Zn3(PO4)2 and the Zn 2+ It is absorbed by the biological HAP matrix of the tubules. The introduction of zinc has been shown to help stabilize dentin and enamel and prevent bacterial invasion. Summary of the invention
[0009] In one aspect, the present disclosure provides a method for treating dental caries comprising administering a composition that results in the deposition of Zn3(PO)4 and / or (NH4)ZnPO4 and / or administering a fluoride-containing zinc substance (e.g., [Zn(NH3)4]F2) that results in the deposition of an inorganic zinc compound.
[0010] In one aspect, the present disclosure provides a method for depositing an inorganic zinc compound. In various embodiments, the inorganic zinc compound is ZnO, Zn(OH)2, or Zn(OH)F. The inorganic zinc compound (e.g., ZnO, Zn(OH)2, or Zn(OH)F) can be deposited on the surface of a carious lesion. The deposition of the inorganic zinc compound (e.g., ZnO, Zn(OH)2, or Zn(OH)F) can be performed by depositing Zn 2+ The reaction occurs when a / NH3 solution (e.g., water or an alcohol-based solution) is diluted into water (e.g., deionized water). An inorganic zinc compound (e.g., ZnO, Zn(OH)2, or Zn(OH)F) can be formed immediately after dilution. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] For a fuller understanding of the nature and objects of the present disclosure, reference should be made to the following detailed description taken in conjunction with the accompanying drawings.
[0012] Figure 1 BSE SEM micrographs of ground HAp surface samples are shown. (A) Zinc nitrate alone, (B) Zinc nitrate followed by dibasic ammonium phosphate, (C) Ammonium phosphate followed by zinc nitrate, (D) Control.
[0013] Figure 2 SEM micrographs of ground HAp surface samples are shown with EDS data showing calcium (red) and zinc (blue). (A) Zinc nitrate alone, (B) Zinc nitrate followed by diammonium phosphate, (C) Ammonium phosphate followed by zinc nitrate, (D) Control.
[0014] Figure 3 BSE SEM micrographs of a cross section of tooth #2 dentin are shown with and without EDS data showing calcium (blue) and zinc (yellow). (A and B) Wide field view 204.8 μm. The green box shows the area selected for the narrow field image. (C and D) Narrow field at 62.5 μm.
[0015] Figure 4 BSE SEM micrographs of a cross section of tooth #3 dentin are shown with and without EDS data showing calcium (blue) and zinc (yellow). (A and B) Wide field view 204.8 μm. The green box shows the area selected for the narrow field image. (C and D) Narrow field at 62.5 μm.
[0016] Figure 5 The sample substrate is shown consisting of ground HAp bonded by epoxy to a silicon support protected by a layer of scotch tape.
[0017] Figure 6Shown are zinc ammonium phosphate powder Zn(NH4)PO4 (A), ground hydroxyapatite (HAp) powder calcium hydroxyapatite on epoxy resin (B), HAp powder treated with zinc nitrate first and then diammonium phosphate (C), HAp powder on epoxy resin treated with diammonium phosphate first and then zinc nitrate (D), and technical grade zinc phosphorite Zn3(PO4)2 (E).
[0018] Figure 7 Shown are (A) minerals formed by adding diammonium phosphate solution to a thin layer of zinc solution on HAp, scale bar 5.0 μm, (B) magnified image, scale bar 1.0 μm. (C) minerals formed by adding zinc nitrate solution to a thin layer of diammonium phosphate solution on HAp, scale bar 5.0 μm, (D) magnified image, scale bar 1.0 μm.
[0019] Figure 8 Shown are ammonium zinc phosphate powder after eleven days of exposure to artificial saliva (top), deionized water (middle), and calculated hopeite map 34869-ICSD (bottom).
[0020] Fig. 9 Shown are the powder diffraction patterns of hopeite (bottom) hopeite standard, calculated 34869-ICSD, (·····) hopeite soaked in water for one week, (---) hopeite soaked in artificial saliva for one week.
[0021] FIG. 10 shows an established method that we have adopted or modified from earlier studies on zinc iodide for preparing solutions containing zinc and fluoride. Dissolution in aqueous ammonia is well known and convenient. Crystals produced by the reaction of ZnI2 and ZnBr2 with gas phase ammonia have been characterized by X-ray crystallography. Recently, a series of zinc amines produced by the reaction of ZnF2 in supercritical ammonia have been shown.
[0022] Fig.11 Various zinc species formed from [Zn(NH3)4]F2 are shown.
[0023] Fig.12 Shown is the powder diffraction pattern of the ZnO product formed upon addition of [Zn(NH3)4]F2(alc) to water. alc = propylene glycol.
[0024] Fig.13 Shown is a SEM micrograph of ZnO formed after adding [Zn(NH3)4]F2(alc) to water. alc = propylene glycol.
[0025] Fig.14 Mineral compounds associated with Streptococcus mutans are shown. The goal is low solubility and conversion of the initial mineral into an increasingly stable source of zinc minerals.
[0026] Fig.15 Shown is hopeite, which is inherently colorless and has potential antimicrobial effects after deposition in dentin.
[0027] Fig.16 Shown is preparation for scanning electron microscopy imaging of synthetic hydroxyapatite (HAp) as a model for the surface of dentinal tubules.
[0028] Fig.17 Shown are x-ray diffraction (left) and scanning electron micrograph (right) of a deposit from a zinc solution followed by application of (NH4)2HPO4(aq).
[0029] Fig.18 Shown are x-ray diffraction (left) and scanning electron micrographs (right) of deposits from zinc phosphate immersed in water.
[0030] Fig.19 Shows F2H 18 Ellipsoid diagram of N4O3Zn, which is [Zn(NH3)4]F2. DETAILED DESCRIPTION
[0031] Although the claimed subject matter will be described according to certain embodiments, other embodiments (including embodiments that do not provide all of the advantages and features described herein) are also within the scope of the present disclosure. Various structural, logical and process step changes may be made without departing from the scope of the present disclosure.
[0032] The range of values is disclosed herein. The range provides a lower limit and an upper limit. Unless otherwise indicated, the range includes all values of magnitude to the minimum value (lower limit or upper limit) within the indicated range and the range between these values.
[0033] The present disclosure provides a safe, non-staining anticaries agent as an alternative to SDF. Embodiments of the agent include antimicrobial activity, the potential to block dentinal tubules (which can reduce dentin hypersensitivity) and promote tissue remineralization. Zinc-based minerals are very suitable for this purpose. The proposed mechanism of zinc ion antimicrobial action includes: 1) binding to microbial membranes, causing bacterial membrane rupture and leakage, 2) extending the growth cycle of bacteria and slowing cell division, and 3) having an affinity for Gram-positive bacteria, including Streptococcus mutans, which is the main bacteria in the caries formation process.
[0034] The potential antimicrobial benefits of zinc deposition have been detailed in several recent studies. One study demonstrated the use of zinc phosphate as a coating for titanium implants, which was shown to be biocompatible, antimicrobial, and a promoter of hydroxyapatite (Hap) formation. Another recent study showed that Zn 2+The composites and ZnO nanoparticles were active against S. mutans. In addition, zinc-loaded HAp nanorods have been shown to have antimicrobial effects against a variety of organisms including S. mutans.
[0035] One area of interest is delivering zinc phosphate directly to the dentinal tubules. Zinc phosphate has a long history in dentistry and was considered a safe and reliable bonding agent until recently, when it was replaced by modern bonding agents with significantly improved mechanical properties and bond strength. However, zinc phosphate minerals may prove to be effective in the treatment of caries. Researchers have shown that zinc phosphate coatings can improve hemocompatibility, cytocompatibility, and antimicrobial activity compared to pure biodegradable zinc, which is thought to release zinc ions too quickly.
[0036] The challenge is to deploy zinc phosphate in dentin as an antimicrobial barrier. Below, we describe the deposition of zinc phosphate mineral that effectively occludes dentinal tubules by crystallizing at tubule openings and assembling crystals within tubules.
[0037] In one aspect, the present disclosure provides a method for treating dental caries comprising administering a composition that results in the deposition of Zn3(PO)4 and / or (NH4)ZnPO4 and / or administering a fluoride-containing zinc substance (e.g., [Zn(NH3)4]F2) that results in the deposition of an inorganic zinc compound.
[0038] Zn3(PO)4 and / or (NH4)ZnPO4 can be formed by mixing various zinc salts and phosphates. For example, dental caries can be treated by applying a composition comprising a zinc salt and then applying a composition comprising a phosphate. In various other embodiments, one or more dental caries can be treated by applying a composition comprising a phosphate and then applying a composition comprising a zinc salt.
[0039] Various zinc salts can be used. For example, the zinc salt is Zn(NO3)2, ZnSO4, Zn(OAc)2, ZnF2, ZnCl2, ZnBr2, ZnI2, Zn(NH3)4]F2, etc., or various combinations thereof.
[0040] Various phosphates can be used. For example, the phosphate is (NH4)2HPO4, (NH4)H2PO4, K3PO4, K2HPO4, KH2PO4, (NH4)2PO3F, etc., or various combinations thereof.
[0041] Without being bound by any particular theory, it is believed that when a composition comprising Zn(NO3)2 is applied and then a composition comprising (NH4)2HPO4 is applied, (NH4)2ZnPO4 is the predominant species formed. Without being bound by any particular theory, it is believed that when a composition comprising (NH4)2HPO4 is applied and then a composition comprising Zn(NO3)2 is applied, Zn3(PO4)2 or Zn3(PO4)2·4H2O (i.e., hopeite) is the predominant species formed. Without being bound by any particular theory, it is believed that (NH4)ZnPO4 converts to hopeite over time.
[0042] In various embodiments, the composition comprises [Zn(NH3)4]F2. The composition comprising [Zn(NH3)4]F2 may also comprise a liquid medium. The liquid medium may be an alcohol (e.g., such as a glycol) and / or water. For example, if the alcohol is a glycol, the glycol may be propylene glycol. In various embodiments, when the glycol is propylene glycol, the liquid medium may also comprise water. For example, the alcohol may be ethanol or methanol. In various embodiments, when the alcohol is ethanol, the liquid medium may also comprise water. In various embodiments, when the alcohol is methanol, the liquid medium may also comprise water. The medium may also comprise ammonia. If the medium is methanol, the ammonia concentration may be 7N. If the medium is ethanol, the ammonia concentration may be 2N. If the medium is water, the ammonia concentration may be 30% by weight of ammonia. If the medium is propylene glycol, the propylene glycol may be saturated with ammonia at STP.
[0043] The composition can be applied to a tooth surface having one or more caries and [Zn(NH3)4]F2 is formed prior to application to the tooth surface or directly to the caries. Without being bound by any particular theory, after application of [Zn(NH3)4]F2, it is believed that an inorganic zinc compound (e.g., ZnO, Zn(OH)2, or Zn(OH)F) will be formed over time and allow the fluoride ions to be gradually released.
[0044] The resulting Zn-based materials (e.g., (NH4)ZnPO4, Zn3(PO4)2, Zn3(PO4)2·4H2O, [Zn(NH3)4]F2) are insoluble and have the desired crystalline and antibacterial properties as described in the examples herein.
[0045] In one aspect, the present disclosure provides a method for depositing an inorganic zinc compound. In various embodiments, the inorganic zinc compound is ZnO, Zn(OH)2, or Zn(OH)F. The inorganic zinc compound (e.g., ZnO, Zn(OH)2, or Zn(OH)F) can be deposited on the surface of a carious lesion. The deposition of the inorganic zinc compound (e.g., ZnO, Zn(OH)2, or Zn(OH)F) can be performed by depositing Zn 2+The reaction occurs when a / NH3 solution (e.g., water or an alcohol-based solution) is diluted into water (e.g., deionized water). An inorganic zinc compound (e.g., ZnO, Zn(OH)2, or Zn(OH)F) can be formed immediately after dilution.
[0046] In various embodiments, the method comprises: 2+ The salt solution is used to deposit inorganic zinc compounds (such as ZnO, Zn(OH)2 or Zn(OH)F). 2+ Non-limiting examples of salts include ZnF2, Zn(NO3)2, ZnSO4, ZnCl2, ZnBr2, ZnI2, and combinations thereof. 2+ The concentration may be 1 to 5 M, including every 0.1 value therebetween and ranges therebetween (e.g., 3.0 M). The concentration of ammonia (NH3) may be 10–30 wt % (relative to the total weight of water and ammonia), including all ranges and values therebetween (e.g., 10 wt %, 20 wt %, or 30 wt %). 2+ The molar ratio of NH3:Zn can be 1:1-10:1 (e.g., 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1). 2+ The molar ratio is 5.5:1.
[0047] The formation of inorganic zinc compounds can be achieved by including Zn 2+ / NH3 solution. For example, if Zn 2+ / NH3 is in water before dilution, or in propylene glycol before dilution, then ZnO will be formed after dilution. In another example, if Zn 2+ / NH3 is in ethanol and water before dilution, then Zn(OH)2 will be formed after dilution. In another example, if Zn 2 + / NH3 is in the water film before dilution, then Zn(OH)F will be formed after dilution.
[0048] The formation of inorganic zinc compounds occurs when Zn 2+ After dilution of Zn / NH3(aq) into water (e.g., deionized water). For example, the dilution should be about 20 times or more (i.e., 50 μL added to 1 mL of water (e.g., deionized water)). Dilution into water can be done directly on the tooth surface. For example, dilution of concentrated Zn / NH3(aq) into water 2+ / NH3(aq), and dilute Zn 2+ / NH3(aq) concentration is at least 20 times.
[0049] In various embodiments, the method comprises: 2+The inorganic zinc compound (e.g., ZnO, Zn(OH)2, or Zn(OH)F) is deposited from a salt solution. Non-limiting examples of alcohols include methanol, ethanol, n-propanol, isopropanol, butanol, sec-butanol, tert-butanol, propylene glycol, ethylene glycol, and combinations thereof. Zn 2+ Examples include, but are not limited to, ZnF2, Zn(NO3) 2、 ZnSO4, ZnCl2, ZnBr2, ZnI2 and their combinations. Zn before dilution 2+ The concentration may be 1 to 5 M, including every 0.1 value therebetween and ranges therebetween (e.g., 3.0 M). The concentration of ammonia may be 1–7 N, including all values and ranges therebetween (e.g., 1, 2, 3, 4, 5, 6, or 7 N). NH3:Zn in solution 2+ The molar ratio may be 1:1-10:1, including every value and range therebetween (e.g., 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1). In various examples, NH3:Zn 2+ The molar ratio is 5.5:1.
[0050] The formation of inorganic zinc compounds (such as ZnO, Zn(OH)2 or Zn(OH)F) occurs when Zn 2+ After diluting / NH3(alcohol) into water (eg, deionized water). For example, the dilution should be about 20 times (ie, add 50 μL to 1 mL of water (eg, deionized water)).
[0051] ZnO, Zn(OH)2 or Zn(OH)F are formed in the caries lesion, among which Zn 2+ / NH3(aq) or Zn 2+ / NH3(alc) can be deposited on carious lesions as an antibacterial agent and / or as a tubule occluding agent.
[0052] The compositions of the present disclosure can be applied to the surface of an individual's teeth in a variety of ways. In various embodiments, the composition is brushed onto / into one or more decayed teeth.
[0053] Any method of the present disclosure can be performed on an individual in need of treatment, wherein the individual suffers from one or more dental caries. The individual in need of treatment can be a human or a non-human mammal. Non-limiting examples of non-human mammals include cows, pigs, rats, cats, dogs, other agricultural animals, pets, service animals, etc.
[0054] The steps of the methods described in the various embodiments and examples of the present disclosure are sufficient to implement the methods of the present invention. Therefore, in one embodiment, the method is essentially composed of a combination of the steps of the methods disclosed herein. In another embodiment, the method is composed of such steps.
[0055] The following statements provide various embodiments of the present disclosure.
[0056] Statement 1. A method for treating one or more caries comprising: i) applying a composition comprising a zinc salt to one or more caries and applying a composition comprising a phosphate to one or more caries, wherein Zn3(PO)4 (and / or its hydrate) and / or (NH4)ZnPO are formed; or ii) applying a composition comprising zinc and fluoride to one or more caries (e.g., wherein an inorganic zinc compound is formed).
[0057] Statement 2. The method according to Statement 1, wherein applying is by brushing the composition onto the surface of the tooth suffering from dental caries.
[0058] Statement 3. The method according to Statement 1 or Statement 2, wherein the zinc salt is Zn(NO3)2, ZnSO4, Zn(OAc)2, ZnF2, ZnCl2, ZnBr2, ZnI2, Zn(NH3)4]F2, etc. or various combinations thereof.
[0059] Statement 4. A method according to any of the preceding statements, wherein the phosphate is (NH4)2HPO4, (NH4)H2PO4, K3PO4, K2HPO4, KH2PO4, (NH4)2PO3F, etc. or various combinations thereof.
[0060] Statement 5. The method according to any one of the preceding statements, wherein the composition comprising a zinc salt is applied before applying the composition comprising a phosphate salt.
[0061] Statement 6. The method according to any one of the preceding statements, wherein the composition comprising a phosphate salt is applied before applying the composition comprising a zinc salt.
[0062] Statement 7. A method according to any of the preceding statements, wherein the concentration of the zinc salt is 30-50 weight % (e.g., 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 or 50 weight %).
[0063] Statement 8. The method according to Statement 7, wherein the concentration of the zinc salt is 35-45 wt % relative to the total weight of the composition.
[0064] Statement 9. The method according to Statement 8, wherein the concentration of the zinc salt is 38-43 weight % relative to the total weight of the composition.
[0065] Statement 10. A method according to any of the preceding statements, wherein the concentration of phosphate is 10-40 weight % (e.g., 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39 or 40 weight %) relative to the total weight of the composition.
[0066] Statement 11. The method according to Statement 10, wherein the concentration of phosphate is 15-35 weight % relative to the total weight of the composition.
[0067] Statement 12. The method according to Statement 11, wherein the concentration of phosphate is 20-30 weight % relative to the total weight of the composition.
[0068] Statement 13. A method according to any one of the preceding statements, wherein Zn3(PO)4 (and / or its hydrate) and / or (NH4)ZnPO4 is formed.
[0069] Statement 14. The method according to any one of the preceding statements, wherein the composition comprising zinc and fluoride comprises [Zn(NH3)4]F2.
[0070] Statement 15. The method of Statement 14, wherein said composition further comprises a liquid medium.
[0071] Statement 16. The method of Statement 15, wherein the liquid medium comprises an alcohol, a glycol, and / or water.
[0072] Statement 17. The method of Statement 16, wherein the glycol is propylene glycol.
[0073] Statement 18. The method of Statement 17, wherein said composition further comprises water.
[0074] Statement 19. The method of Statement 16, wherein the alcohol is methanol or ethanol.
[0075] Statement 20. The method of Statement 19, wherein the alcohol is methanol.
[0076] Statement 21. The method of Statement 20, wherein said composition further comprises water.
[0077] Statement 22. The method of Statement 19, wherein said alcohol is ethanol.
[0078] Statement 23. The method of Statement 22, wherein said composition further comprises water.
[0079] Statement 24. A composition comprising [Zn(NH3)4]F2.
[0080] Statement 25. The composition of Statement 24, wherein said composition further comprises a liquid medium.
[0081] Statement 26. The composition of Statement 25, wherein the liquid medium comprises an alcohol, a glycol, and / or water.
[0082] Statement 27. The composition of Statement 26, wherein said glycol is propylene glycol.
[0083] Statement 28. The composition of Statement 27, wherein said composition further comprises water.
[0084] Statement 29. The composition of Statement 26, wherein the alcohol is methanol or ethanol.
[0085] Statement 30. The composition of Statement 29, wherein the alcohol is methanol.
[0086] Statement 31. The composition of Statement 30, wherein said composition further comprises water.
[0087] Statement 32. The composition of Statement 29, wherein said alcohol is ethanol.
[0088] Statement 33. The composition of Statement 32, wherein said composition further comprises water.
[0089] Statement 34. A method for preparing an inorganic zinc compound comprising: diluting with water a mixture containing Zn 2+ / NH3 solution, wherein the dilution results in the formation of ZnO, Zn(OH)2 and / or Zn(OH)F.
[0090] Statement 35. The method according to statement 34, wherein Zn 2+ / NH3 solution is an aqueous ammonia solution.
[0091] Statement 36. The method according to Statement 34 or Statement 35, wherein Zn 2 From ZnF2, Zn(NO3)2, ZnSO4, ZnCl2, ZnBr2, ZnI2 or a combination thereof.
[0092] Statement 37. A method according to any one of Statements 34-36, wherein Zn 2+ The concentration is 1 to 5M (eg 3M).
[0093] Statement 38. The method of any one of Statements 34-37, wherein the concentration of ammonia is from 10 to 30 weight % relative to the total weight of water and ammonia.
[0094] Statement 39. A method according to any one of Statements 34-38, wherein the solution contains NH3:Zn 2+ The molar ratio is 1:1-10:1.
[0095] Statement 40. The method according to statement 34, wherein Zn 2+ / NH3 solution is alcoholic ammonia solution.
[0096] Statement 41. The method of Statement 40 wherein the alcohol of the alcoholic ammonia solution is selected from the group consisting of methanol, ethanol, n-propanol, isopropanol, butanol, sec-butanol, tert-butanol, propylene glycol, ethylene glycol, and combinations thereof.
[0097] Statement 42. The method according to Statement 40 or Statement 41, wherein Zn 2+ From ZnF2, Zn(NO3)2, ZnSO4, ZnCl2, ZnBr2, ZnI2 or a combination thereof.
[0098] Statement 43. A method according to any one of Statements 34 or 40-42, wherein Zn 2+ The concentration is 1 to 5M (eg 3M).
[0099] Statement 44. The method according to any one of Statements 40-43, wherein the concentration of ammonia is 1 to 7N.
[0100] Statement 45. A method according to any one of Statements 40-44, wherein the solution contains NH3:Zn 2+ The molar ratio is 1:1-10:1.
[0101] Statement 46. A method according to any one of Statements 40-45, wherein before dilution the Zn 2+ / NH3 solution is applied to the surface of the tooth or the caries in the tooth.
[0102] Statement 47. A method according to any one of Statements 40-46, wherein the mixture containing Zn is applied to the surface of the tooth or to the dental caries with water. 2+ / NH3 solution was diluted at least 20 times.
[0103] Statement 48. The method of any one of Statements 40-47, wherein said method occurs in the oral cavity of a subject.
[0104] The following examples are provided to illustrate the present disclosure. They are not intended to be limiting in any way.
[0105] Example 1
[0106] This example provides a description of methods of making and using the zinc-based materials of the present disclosure.
[0107] Dentin blocks prepared from human permanent molars were topically treated by sequential application of aqueous zinc nitrate and ammonium phosphate solutions. Field emission scanning electron microscopy (FE-SEM) images and energy dispersive X-ray scattering (EDS) revealed the presence of abundant crystallized and colorless zinc mineral deposits both within the dentinal tubules and on the dentine surface. Parallel experiments on ground hydroxyapatite (HAp) surfaces using XRD analysis showed that the initial mineral deposited could be either ammonium zinc phosphate ((NH4)ZnPO4) or zinc phosphate (Zn3(PO4)2), depending on the reaction conditions. The results provide a way to optimize the deposition of ionic zinc directly into dentinal tubules in carious lesions, which could serve as an antimicrobial agent for caries inhibition, possible lesion remineralization, and alleviation of hypersensitivity.
[0108] Two experimental designs were used. In the first experiment, the solution was applied to non-caries dentin, and the surface and tubule cross-sections were evaluated using SEM and EDS analysis. In the second experiment, the solution was applied to a milled HAp coating on a silicon substrate, and data were collected using scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and X-ray powder diffraction (XRD).
[0109] Ground Hap was donated. Zinc nitrate (Zn(NO3)2·6H2O) was purchased from Strem chemicals. Zinc phosphate (Zn3(PO4)2·x H2O) was purchased from Alfa Aesar (lot number: M09E004, x=3.64). Monoammonium phosphate ((NH4)H2PO4) was purchased from Honeywell / Fluka (lot number: J0930), and diammonium phosphate ((NH4)2HPO4) was purchased from Fischer Chemicals (lot number: 972377). Ammonium hydroxide ACS (28.0-30.0% NH3) was purchased from Alfa Aesar (lot number: P05F004). Phosphate buffered saline (PBS) was purchased from Fisher Scientific, Waltham, MA, USA. All chemicals were used as received.
[0110] Stock solutions of 42% (w / w) zinc nitrate hexahydrate and 24% (w / w) diammonium phosphate were prepared in deionized (DI) water, 5 ml of each solution was used for the experiments described below. It should be noted that if the solutions were directly combined in equal amounts, the molar ratio of the reactants would be 1:1. The epoxy resin used to fix the HAp powder to the substrate was Devcon 5 Transparent epoxy resin. Artificial saliva (1700-0305) was purchased from Pickering Laboratories and used as received. Artificial saliva 1700-0305: (Pickering Laboratories); sodium carboxymethylcellulose 10.00 g / L; potassium dihydrogen phosphate 0.326 g / L; potassium chloride 0.625 g / L; potassium dihydrogen phosphate 0.804 g / L; magnesium chloride hexahydrate 0.059 g / L; calcium chloride dihydrate 0.166 g / L; methyl paraben 2.00 g / L.
[0111] Synthesis of ammonium zinc phosphate. Ammonium zinc phosphate ((NH4)ZnPO4) was synthesized by the method of Baitahe with some modifications. Briefly, 5.97 g Zn(NO3)2·6H2O was weighed into a 40 ml beaker. To this was added 21 ml 1M (NH4)H2PO4 and stirred, followed by the addition of 20 ml 2M NH3 (aq, 28.0-30.0%). The resulting slurry was stirred vigorously for 15 min. The product was then collected by filtration, washed with deionized water and transferred to a watch glass to dry. As a modification, an aging step was added, in which the product was resuspended and stirred in deionized water overnight, collected by filtration, washed with acetone, then washed with ether and allowed to dry. The resulting powder was moderately free-flowing. XRD analysis showed that the product scan matched that of the previously reported ammonium zinc phosphate 85444-ICSD.
[0112] Dentin samples: Preparation and application of experimental solutions. Ethical approval for the use of extracted human teeth was obtained in accordance with the guidelines of the New York University College of Dentistry. Four extracted healthy human third molars were stored in a 0.1% thymol solution at 4°C to prevent post-extraction microbial growth. The teeth were then removed from the thymol solution, soaked in deionized water for 30 minutes, and then rinsed with deionized water. The teeth were then immersed in 1X PBS, which was diluted from a 10X PBS solution using deionized water. The teeth were placed in the 1X PBS solution for 7 days before the experiment.
[0113] All teeth were cut tangentially along the occlusal surface using a Buehler Isomet diamond blade (Lake Bluff, IL, USA) to a depth of approximately 1 mm to the tip of the shortest cusp to form a flat occlusal surface. The cusp tip was discarded. The tooth was then cut to approximately 2 mm from the tip of the deepest occlusal central groove to remove the occlusal enamel and expose the underlying dentin. This cut produced two planes for each tooth treated experimentally: 1) the concave surface of the 2 mm flat dentin disk and 2) the flat occlusal surface of the remaining body of the tooth. The location and direction of the cut were selected to produce slices perpendicular to the direction of the dentinal tubules. 35% phosphoric acid (Fisher Scientific, Waltham, MA, USA) was applied for 15 seconds and then rinsed with deionized water for 15 seconds to remove the smear layer on all treated surfaces. Excess moisture was removed by blowing with a gentle stream of compressed air for 5 seconds.
[0114] The experimental solution was applied to the three occlusal surfaces of the three dentin discs and the rest of the body of each corresponding tooth. A fourth tooth sample was used as a control. Disc / Body 1: 42% zinc nitrate was applied to both surfaces using a microbrush in a scrubbing motion for 15 seconds. After two minutes, the sample was immersed in 1X PBS. Disc / Body 2: 42% zinc nitrate was applied to both surfaces using a scrubbing motion for 15 seconds. After two minutes, a gentle stream of compressed air was used for 5 seconds to remove visible liquid on the surface. Next, 24% diammonium phosphate solution was applied to both surfaces using a scrubbing motion for 15 seconds. After two minutes, the sample was immersed in 1X PBS solution. Disc / Body 3: The same method as Disc 2 was used, except that the diammonium phosphate solution was applied first, followed by the zinc nitrate. Disc / Body 4: No experimental solution was applied. After the smear layer was removed, the disc was immediately immersed in the PBS solution.
[0115] Dentin samples: Preparation for SEM and EDS analysis. After 24 hours, four flat disc samples were removed from the PBS solution and air-dried for three days. The flat discs were adhered to an aluminum stub with carbon paint and then carbon-coated using a Desk V carbon evaporator (Denton Vacuum, LLC, Moorestown, NJ USA). Each tooth in the four main dentin samples was embedded in polymethyl methacrylate and then cut in the mesial-distal direction along the long axis of the tooth and through the center of each tooth. This produced a dentin cross-section sample with the long axis of the tubules located in the surface plane for SEM analysis. The samples were adhered to an aluminum stub with carbon paint and then carbon-coated using a Desk V carbon evaporator (Denton Vacuum, LLC, Moorestown, NJ USA) for SEM analysis. The concave surface of the disc was used to study the treated dentin surface. Mesial-distal cut teeth were used to study the penetration of the treated material into the dentinal tubules.
[0116] Ground HAp samples: mineral formation. The ground HAp coated substrate was treated with a few drops of zinc nitrate stock solution delivered by a Pasteur pipette. The solution was gently spread to form a film on the HAp surface. After 5 minutes, the excess solution was wicked away using a Kimwipe. A few drops of diammonium phosphate stock solution were then added to the sample and allowed to sit for 3 minutes before the excess solution was wicked away and the sample was washed with deionized water and dried overnight. The dried sample was then characterized by SEM or XRD.
[0117] Preparation of zinc phosphate on planar substrates: Preparation for SEM, EDS and XRD analysis. For SEM measurements, an aluminum backed carbon sheet (Ted Pella, 16091-12) was applied to an aluminum pin stub (Ted Pella, 16111-9) platform. HAp or zinc phosphate in powder form was applied to the exposed bonded carbon sheet surface. The selected solution for mineral deposition was applied to the HAp layer using a Pasteur pipette. After drying in air, the samples were sputter coated with gold for SEM and EDS analysis.
[0118] For XRD measurements, flat samples were prepared as substitutes for natural or treated dentin surfaces. The natural surface mimic consisted of HAp powder anchored by epoxy on a silicon wafer (001 cut, 1 cm x 1 cm) protected with transparent tape. To prepare the HAp substrate, liquid 5-min epoxy (Devcon, transparent) was deposited on the tape and a sufficient excess of ground Hap was compacted on the epoxy to ensure that the exposed substrate surface was rich in HAp. After drying, the assembly was gently tapped with a spatula to remove unbound HAp and then washed with deionized water to further remove loosely bound HAp. The wafer was adhered to a pin stub base. The base with the sample was carefully fixed to the sample holder in the instrument. The zinc phosphate samples on HAp were soaked in deionized water for one week, and then the samples were washed with deionized water, washed with acetone, and dried. A second set of zinc phosphate samples on HAp were soaked in artificial saliva for one week. The samples were then washed with deionized water, followed by acetone, and then dried prior to SEM and XRD analysis.
[0119] Bulk mineral samples: Effect of solution on minerals. Two portions of ammonium zinc phosphate powder (1 mg each) were suspended in approximately 1 ml of deionized water and 1 ml of artificial saliva, respectively, in test tubes sealed with rubber stoppers for 11 days. At the end of the immersion period, the powders were resuspended by ultrasonic treatment, transferred to Eppendorf centrifuge tubes, and centrifuged at 8000 rpm for 6 minutes. The supernatant was discarded. 1 ml of the sample of deionized water was added to each sample, then vortexed to mix, and the centrifugation step was repeated. The supernatant was removed and the resuspension / centrifugation step was repeated. Finally, the samples were resuspended in 1 ml of methanol and then resuspended twice with ether, followed by centrifugation at each step. The samples were then dried in air, loaded into 0.5 mm Kapton capillaries and mounted on a magnetic base for powder XRD analysis.
[0120] Two samples of zinc phosphate powder (55 mg in 1 ml of deionized water and 60 mg in 1 ml of artificial saliva) were placed in test tubes sealed with parafilm for 1 week. The samples were processed using standard methods and stored in vials after drying. The powder samples were adhered to epoxy resin on a Si support as described above for Hap.
[0121] Dentin samples: SEM images and EDS analysis of dentin samples were obtained using a Hitachi S-3500N SEM (Hitachi, Tokyo, Japan) in backscattered electron (BSE) mode and a Bruker XFlash 6110 energy dispersive X-ray spectrometer (Bruker, Billerica, MA, USA), respectively. ESPRIT version 2.1 was used to capture BSE and EDS images. All images were taken under high vacuum, 20 kV, and a working distance of 15 mm. For EDS images, the following settings were used in the ESPRIT software: map display filter: smoothing = 7, surface color blending: enhanced.
[0122] Powdered HAp samples: SEM images and EDS analysis of HAp were obtained using a Carl-Zeiss Gemini 300 field emission scanning electron microscope (FE-SEM) and a Bruker XFlash 6160, respectively.
[0123] Powdered samples were layered on a zero-background Si substrate on a PanAnalytical X'Pert XRD instrument. All scans used a curved crystal monochromator with the following settings: 45 kV, 40 mA, step size 0.013° (2θ), 99.45 s per step, ranging from 10-45° (PanAnalytical, Malvern Panalytical, Almelo, The Netherlands).
[0124] XRD capillary data were acquired on a Bruker D8 DISCOVER GADDS microdiffractometer equipped with a VANTEC-2000 area detector. The X-rays generated by the sealed Cu tube were monochromated by a graphite crystal and collected by a 0.5 mm MONOCAP (λ, Cu-Kα = ) collimation. The sample detector distance was 150 mm and the exposure time for each run was 300-1500 seconds. The sample position was adjusted by a manual control box with the help of the camera and the alignment laser. The data were integrated by the XRD2EVAL program in the Bruker PILOT software. The raw files were converted to UXD format by DIFFRACplus File Exchange and then analyzed by the WINPLOTR program.
[0125] Dentin disc surface samples: SEM / EDS characterization after treatment. The intaglio surface of the disc samples was imaged in BSE mode and EDS was used to characterize the elemental distribution. Images were acquired at 20 kV, a working distance of 15 mm, and field widths of 122.88 μm and 35.84 μm. Spectra and elemental quantification were obtained for all samples. SEM BSE images are shown in Figure 2. Figure 1 As shown in the figure, and the corresponding EDS image is shown in Figure 2 Calcium is labeled in red and zinc is labeled in blue. Phosphorus (not shown) was detected uniformly across the field width of all samples, indicating that phosphorus is present in both the crystal and the dentin.
[0126] Disc 1: 42% zinc nitrate. Various crystal morphologies were observed ( Figure 1 A and 2A), where the largest crystals are oval, flat, and hexagonal, up to about 6 μm long by about 2 μm wide. Other crystals are tiny needles, about 1 μm long. EDS visually confirmed the presence of zinc in both types of crystals.
[0127] Disc 2: 42% zinc nitrate, then 24% diammonium phosphate. Main types ( Figure 1 B and 2B) are fine needle-like clusters with a length of about 1 μm. Spectral analysis and quantitative analysis show that the relative abundance of zinc atoms on this surface is the highest.
[0128] Disc 3: 24% diammonium phosphate, then 42% zinc nitrate. The crystal morphology is multiphase ( Figure 1 C and 2C). Thin needles with a length of 1-2 μm and small flat rectangular types with the longest dimension generally being 1 μm or less are present.
[0129] Disc 4: Control. No precipitate or zinc was observed on the control surface ( Figure 1 D and 2D).
[0130] Dentin bulk samples, cross-sectioned to visualize the longitudinal deposition of zinc minerals: SEM / EDS characterization after processing. The surfaces of the mesial-distal cross-sectioned samples were imaged in BSE mode and characterized with EDS. Images were taken for each sample using 20 kV, a working distance of 15 mm, and field widths of 204.8 μm and 62.46 μm. Spectra and elemental quantification were obtained for all samples. Calcium and zinc are marked in blue and yellow, respectively. Phosphorus (not shown) was uniformly detected across the field width of all samples, indicating that phosphorus is present in both the crystal and dentin.
[0131] Considerable amounts of intratubular precipitates were detected on teeth 2 and 3. Images of tooth 1 (42% zinc nitrate only) and tooth 4 (control) are not shown. Only a few crystals were detectable on disc 1, with the furthest penetration being approximately 40 μm from the dentin surface. No precipitates or zinc were detected on the control.
[0132] Tooth 2: 42% zinc nitrate followed by 24% diammonium phosphate. Crystals containing zinc and phosphorus were found in almost every tubule to a depth of about 120 μm ( Figure 3 ). The crystal morphology seen in the narrow field image appears fairly uniform throughout the sample. Most crystals are 2-3 μm in length, which is very close to the width of the dentinal tubules in which they are embedded.
[0133] Tooth 3: 24% diammonium phosphate, then 42% zinc nitrate. Crystals containing zinc and phosphorus were found 50 μm from the tubule opening ( Figure 4 ). Most of the crystals are concentrated at the openings of the tubules. The type of crystals that block the openings of the tubules presents a different morphology than the crystals inside.
[0134] HAp sample: zinc phosphate deposition on HAp (zinc phosphate / HAp) XRD and SEM. The silicon plate was protected by applying tape. A thin layer of epoxy resin was deposited on the tape surface. The ground HAp was then gently pressed onto the epoxy surface and the epoxy was allowed to cure for about 30 minutes ( Figure 5 ).
[0135] Excess HAp was removed by tapping the inverted Si support. The presence of excess unbound mineral after epoxy curing would protect the active mineral surface from being covered by the adhesive.
[0136] Solutions containing zinc and phosphate were combined to deposit zinc phosphate minerals. Mineral deposition on HAp was performed by sequentially adding 42% zinc nitrate followed by 24% diammonium phosphate (or in reverse order). After the zinc nitrate solution was added, the excess liquid was wicked away using a Kimwipe to leave a thin film of the solution on the HAp. The ammonium phosphate solution in the liquid film naturally exceeded the zinc nitrate. After 10 minutes, the liquid was wicked away again, and the sample was washed with deionized water and allowed to dry for at least two hours.
[0137] XRD data showed that ammonium zinc phosphate ((NH4)ZnPO4, 85444-ICSD) was formed on the ground HAp (151414-ICSD) ( Figure 6 ). The ammonium zinc phosphate peaks appear at 2θ values of 14, 19, 20, 28, and 36. The other peaks belong to the ground HAp, either alone or overlapping with the ammonium zinc phosphate. In the reverse order of reagent addition, i.e., 24% diammonium hydrogen phosphate was applied to the HAp surface followed by 42% zinc nitrate, the mineral product was phosphorite Zn3(PO4)2·4H2O, and its powder pattern was determined (34869-ICSD)( Figure 6 ).
[0138] The corresponding SEM images of the two minerals deposited on HAp clearly show the cauliflower-like structure of ammonium zinc phosphate and the flower-like structure of zinc oxide ( Figure 7 ).
[0139] Fate of zinc minerals in aqueous media: ammonium zinc phosphate was immersed in deionized water and artificial saliva. The key to understanding the role of zinc phosphate in dentinal tubules is the nature of its transformation when exposed to the ion-rich salivary environment (such as in open dentinal tubules) for a long time. Ammonium zinc phosphate powder immersed in artificial saliva and water for 11 days was converted to zinc phosphate ( Figure 8 ).
[0140] The peaks at 2θ: 17, 17.5, 18 and 31.8 belong to hopeite (34869-ICSD). In this immersion experiment, the transformation of ammonium zinc phosphate to the more stable phase, hopeite, was more pronounced in deionized water but negligible in artificial saliva.
[0141] Pyrophosphorite does not undergo morphological changes in aqueous media. Except for the broadening of the peak, its powder diffraction pattern remains essentially unchanged ( Fig. 9 ). The full width at half maximum (2θ) of the (241) peak at 31.3 for hopeite in deionized water is 0.368, and for hopeite in artificial saliva is 0.487.
[0142] Applying the Scherrer equation,
[0143]
[0144] (where B is the full width at half maximum of the peak, K is a constant of 0.89, λ is the wavelength of the radiation 0.154 nm, L is the crystallite size, and θ is the angle of incidence of the radiation 12.0 degrees) yielding L values of 22.4 nm and 16.8 nm, respectively. For the dried samples, the apparent crystallite size differences appear to decrease over time, possibly due to changes in hydration.
[0145] The above results support the feasibility of using zinc, which has known antimicrobial properties, to treat dental caries. A dentin block model was used to study the deposition of zinc phosphate minerals in response to aqueous zinc ions and aqueous phosphate ions on the dentin surface and at the openings and inside the dentinal tubules. The result was a rapid occlusion of the open tubules. The formation and fate of the associated zinc phosphate minerals in an aqueous environment were examined on the surface of ground HAp as a dentin substitute. This method facilitated product analysis by XRD and SEM, and the results showed that the order of ion addition determined the composition of the mineral and its deposition area.
[0146] The sequential application of aqueous zinc ions followed by phosphate ions to the dentin surface resulted in each solution being absorbed into the tubules and mixing within the tubules to precipitate zinc phosphate. SEM and EDS analysis showed that the sequential addition of zinc followed by phosphate produced zinc phosphate mineral in the form of 2-3 micron-sized crystals that were fairly uniformly distributed within the dentinal tubules to a depth of 120 microns. When the phosphate solution was applied first and then zinc (phosphate followed by zinc), smaller needle-shaped crystals were more prevalent on the dentin surface, where they blocked the tubule openings.
[0147] Studies have shown that the mineral component of peritubular dentin is carbonated HAp lacking calcium. For convenience, this study used the ground HAp substrate as an analog of the peritubular dentin surface to evaluate the deposition of zinc phosphate minerals in the mixed solution.
[0148] Parallel experiments using ground HAp as a substitute for dentin provided insight into the conditions of mineral formation and transformation. In this system, a layer of HAp was exposed to an aqueous medium while being attached to an inert underlying silicon substrate by an epoxy layer and tape. Application of a zinc salt solution followed by a phosphate solution (zinc then phosphate) produced a stable mineral phase, ammonium zinc phosphate, which was attached to the HAp. Excess zinc nitrate solution was wicked away, leaving a film whereby diammonium phosphate ions were then in excess. These conditions favored the formation of the observed products.
[0149] (NH4)2HPO4(excess)+Zn(NO3)2→(NH4)ZnPO4+NH4 + +H + +2NO3 - +n(NH4)2HPO4
[0150] When the order of reagent addition is reversed, the excess ammonium phosphate solution is aspirated and then the zinc nitrate is added, nominally resulting in a reaction with the following stoichiometry:
[0151] Zn(NO3)2(excess)+2(NH4)2HPO4→Zn3(PO4)2·4H2O+4NH4 + +2H + +6NO3 - +n Zn(NO3)2
[0152] Studies on SDF and calcium phosphate have shown that solutions applied to the dentin surface readily penetrate into the open dentinal tubules. The use of calcium phosphate as an occlusal agent has not been further developed. The result of SDF absorption is the presence of silver deep within the tubules. The antimicrobial efficacy of SDF requires that the silver deposits remain within the tubules for a prolonged period of time to exert a sustained bactericidal effect. The deposition of silver in SDF may involve the mixed absorption of ions by HAp and the formation of insoluble silver metal nanoparticles under the photoreduction of silver phosphate by ambient light.
[0153] The deposition and permanence of zinc requires different conditions than silver. Since direct uptake of zinc ions from solution by HAp is inherently low, zinc deposition is best achieved through de novo mineralization, which can be achieved through the formation of zinc phosphate. The specific order of addition of zinc then phosphate reagents to the dentin surface favors the deposition of zinc ammonium phosphate within the dentinal tubules. This approach produces the deepest tubule penetration depth (120 microns) by zinc and the highest density of occluded tubules by crystals.
[0154] In aqueous solution, ammonium zinc phosphate ((NH4)ZnPO4) transforms over time into the more stable phosphorite phase, Zn3(PO4)2·4H2O( Figure 6 ). This process is attenuated in artificial saliva, presumably because the phosphate ions create an equilibrium in which the phosphate:zinc ratio is high, which favors (NH4)ZnPO4 over Zn3(PO4)2. However, in clinical applications, zinc phosphate can be the final phase that persists in treated teeth, providing a long-term reservoir of zinc. In addition, it can undergo ion exchange with calcium ions to produce a calcium phosphate phase in the dentinal tubules, which can be used for remineralization of carious tissue, a desirable outcome. These results suggest that zinc phosphate can be produced to occlude dentinal tubules, increase dentin hardness, and reduce the permeability of exposed dentin. No discoloration was observed in any of the treated dentin in this experiment. Zinc phosphate is known to have antimicrobial properties. In an application as a coating for titanium implants, zinc phosphate has been shown to be biocompatible, antimicrobial, and a promoter of HAp formation.
[0155] These results indicate that topical application of zinc and phosphate solutions produces mineral deposition on the dentin surface and within the tubules. Experiments performed on HAp surfaces allowed the identification of colorless zinc phosphate minerals that are a function of the reaction stoichiometry and the nature of the mineral transformation upon prolonged contact with aqueous media. The scheme of mineral formation and the nature of the products may prove to be well suited for the treatment of caries or the alleviation of hypersensitivity due to their antimicrobial activity and aesthetic acceptability.
[0156] Without being bound by any particular theory, it is believed that the zinc ammonium phosphate precipitate is particularly active against S. mutans because it is a source of zinc ions. In addition, this new zinc-based dentin treatment opens up a number of other areas of research, including mechanical effects on resin adhesive bonding, long-term color stability of dentin after application, and improved protocols for increasing crystal penetration depth or density.
[0157] Example 2
[0158] The purpose of the present disclosure is to deposit (1) zinc phosphate, (2) ammonium zinc phosphate, and then (3) zinc fluoride in dentin. The following is a summary of the precursors and the products that have been produced:
[0159] 1)Zn(NO3)2·6H2O+(NH4)2HPO4→Zn(NH4)PO4 and Zn3(PO4)2
[0160] 2)Zn(NO3)2·6H2O+ZnF2·4H2O→2[ZnF(H2O)5]NO3
[0161] 3) Zn(NO3)2·6H2O+Na2FPO3→ZnFPO3, the product is known.
[0162] 4)ZnF2·4H2O+NH3(MeOH)→[Zn(NH3)4]F2,
[0163] 5) ZnF2·4H2O+NH3(EtOH)→[Zn(NH3)4]F2, which is expected to be consistent with reaction 4
[0164] 6)[Zn(NH3)4]F2+H2O→ZnO+2(NH4)F+2NH3(aq)
[0165] Zinc tetraammine difluoride has been crystallized and structurally characterized for the first time. The synthesis itself is simple and provides a facile route to the product in solid crystalline form. The conversion to zinc oxide is very clean and potentially quantitative. This is the core reaction of our technology as it potentially provides both zinc oxide as an antimicrobial agent and fluoride as a remineralization aid.
[0166] Example 3
[0167] Also provided is the delivery of ZnO to dentinal tubules.
[0168] A method for preparing Zn in aqueous ammonia is described. 2+ A new method for ZnO deposition from salt solutions. 2+The salt may be, for example, ZnF2, Zn(NO3)2, ZnSO4, ZnCl2, ZnBr2 or ZnI2. The concentration of ammonia (NH3) may be 10 wt%, 20 wt% or 30 wt%. Other percentages may also be suitable. 2+ The molar ratio can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1-10:1.
[0169] A method for preparing a Zn-containing alcohol from 2+ A novel method for depositing ZnO from a solution of a salt. The alcohol can be methanol, ethanol, n-propanol, isopropanol, butanol, sec-butanol, tert-butanol, propylene glycol or ethylene glycol. Zn 2+ The salt may be, for example, ZnF2, Zn(NO3)2, ZnSO4, ZnCl2, ZnBr2 or ZnI2. The concentration of ammonia (NH3) may be 1N, 2N-N. Other concentrations may also be suitable. 2+ The molar ratio can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1-10:1.
[0170] Zn 2+ The formation of ZnO occurs after dilution of the NH3(aq) solution in deionized water. The dilution should be about 20 times, i.e., 50 microliters of the solution is added to 1 ml of deionized water.
[0171] Zn 2+ The formation of ZnO occurs after dilution of the NH3(alc) solution in deionized water. The dilution should be about 20 times, i.e., 50 microliters of the alcohol solution is added to 1 ml of deionized water.
[0172] ZnO is formed in the caries lesion, of which Zn 2+ / NH3(aq) or Zn 2+ / NH3(alc) deposits on carious lesions as an antibacterial agent.
[0173] ZnO is formed in caries lesions, of which Zn 2+ / NH3(aq) or Zn 2+ / NH3(alc) is deposited on carious lesions as a tubule occluding agent.
[0174] Example 4
[0175] The following data comes from F2H 18 Crystallographic information of N4O3Zn.
[0176]
[0177]
[0178]
[0179]
[0180]
[0181]
[0182]
[0183]
[0184]
[0185]
[0186]
[0187]
[0188]
[0189]
[0190]
[0191]
[0192]
[0193]
[0194]
[0195]
[0196]
[0197]
[0198]
[0199]
[0200]
[0201]
[0202]
[0203]
[0204]
[0205]
[0206]
[0207]
[0208]
[0209]
[0210]
[0211]
[0212]
[0213]
[0214]
[0215]
[0216]
[0217]
[0218]
[0219]
[0220]
[0221]
[0222]
[0223]
[0224]
[0225]
[0226]
[0227]
[0228]
[0229]
[0230]
[0231]
[0232]
[0233] Although the present disclosure has been described with respect to one or more specific embodiments and / or examples, it should be understood that other embodiments and / or examples of the present disclosure may be made without departing from the scope of the present disclosure.
Claims
1. A method for treating one or more dental caries, comprising: applying a composition comprising a zinc salt to the one or more decayed teeth, and applying a composition comprising phosphate to the one or more decayed teeth, wherein Zn3(PO)4 (and / or its hydrate) and / or (NH4)ZnPO4 are formed; or A composition comprising zinc and fluoride is applied to the one or more decayed teeth.
2. The method of claim 1, wherein the applying is by brushing the composition onto the surface of a tooth suffering from caries.
3. The method of claim 1, wherein the zinc salt is Zn(NO3)2, ZnSO4, Zn(OAc)2, ZnF2, ZnCl2, ZnBr2, ZnI2, Zn(NH3)4]F2 or various combinations thereof.
4. The method of claim 1, wherein the phosphate is (NH4)2HPO4, (NH4)H2PO4, K3PO4, K2HPO4, KH2PO4, (NH4)2PO3F or various combinations thereof.
5. The method of claim 1, wherein the composition comprising a zinc salt is applied prior to applying the composition comprising a phosphate salt.
6. The method of claim 1, wherein the composition comprising a phosphate salt is applied prior to applying the composition comprising a zinc salt.
7. The method according to claim 1, wherein the concentration of the zinc salt is 30-50 wt% relative to the total weight of the composition.
8. The method according to claim 7, wherein the concentration of the zinc salt is 35-45 wt% relative to the total weight of the composition.
9. The method according to claim 8, wherein the concentration of the zinc salt is 38-43 wt% relative to the total weight of the composition.
10. The method according to claim 1, wherein the concentration of the phosphate is 10-40 wt% relative to the total weight of the composition.
11. The method according to claim 10, wherein the concentration of the phosphate is 15-35 wt% relative to the total weight of the composition.
12. The method according to claim 11, wherein the concentration of the phosphate is 20-30 wt% relative to the total weight of the composition.
13. The method according to claim 1, wherein Zn3(PO)4 (and / or its hydrate) and / or (NH4)ZnPO4 are formed.
14. The method of claim 1, wherein the composition comprising zinc and fluoride comprises [Zn(NH3)4]F2.
15. The method of claim 14, wherein the composition further comprises a liquid medium.
16. The method of claim 15, wherein the liquid medium comprises an alcohol, a glycol and / or water.
17. The method of claim 16, wherein the glycol is propylene glycol.
18. The method of claim 17, wherein the composition further comprises water.
19. The method of claim 16, wherein the alcohol is methanol or ethanol.
20. The method of claim 19, wherein the alcohol is methanol.
21. The method of claim 20, wherein the composition further comprises water.
22. The method of claim 19, wherein the alcohol is ethanol.
23. The method of claim 22, wherein the composition further comprises water.
24. A composition comprising [Zn(NH3)4]F2.
25. The composition of claim 24, wherein the composition further comprises a liquid medium.
26. The composition of claim 25, wherein the liquid medium comprises an alcohol, a glycol and / or water.
27. The composition of claim 26, wherein the glycol is propylene glycol.
28. The composition of claim 27, wherein the composition further comprises water.
29. The composition of claim 26, wherein the alcohol is methanol or ethanol.
30. The composition of claim 29, wherein the alcohol is methanol.
31. The composition of claim 30, wherein the composition further comprises water.
32. The composition of claim 29, wherein the alcohol is ethanol.
33. The composition of claim 32, wherein the composition further comprises water.
34. A method for preparing an inorganic zinc compound, comprising: Dilute with water containing Zn 2+ / NH3 solution, wherein said dilution results in the formation of said inorganic zinc compound, wherein said inorganic zinc compound is ZnO, Zn(OH)2 and / or Zn(OH)F.
35. The method according to claim 34, wherein the Zn 2+ / NH3 solution is an aqueous ammonia solution.
36. The method of claim 34, wherein Zn 2+ From ZnF2, Zn(NO3)2, ZnSO4, ZnCl2, ZnBr2, ZnI2 or a combination thereof.
37. The method of claim 34, wherein Zn 2+ The concentration is 1 to 5M.
38. The method according to claim 34, wherein the concentration of ammonia is 10 to 30 wt% relative to the total weight of water and ammonia.
39. The method according to claim 34, wherein the solution contains NH3:Zn 2+ The molar ratio is 1:1-10:
1.
40. The method according to claim 34, wherein the Zn 2+ / NH3 solution is alcoholic ammonia solution.
41. The method of claim 40, wherein the alcohol of the alcoholic ammonia solution is selected from the group consisting of methanol, ethanol, n-propanol, isopropanol, butanol, sec-butanol, tert-butanol, propylene glycol, ethylene glycol, and combinations thereof.
42. The method of claim 40, wherein Zn 2 From ZnF2, Zn(NO3)2, ZnSO4, ZnCl2, ZnBr2, ZnI2 or a combination thereof.
43. The method of claim 40, wherein Zn 2+ The concentration is 1 to 5M.
44. The method of claim 40, wherein the concentration of ammonia is 1 to 7N.
45. The method according to claim 40, wherein the solution contains NH3:Zn 2+ The molar ratio is 1:1-10:
1.
46. The method of claim 34, wherein the Zn-containing 2+ / NH3 solution is applied to the surface of the tooth or the caries in the tooth.
47. The method according to claim 46, wherein the Zn-containing 2 + / NH3 solution was diluted at least 20 times.
48. The method of claim 34, wherein the method is performed in the oral cavity of a subject.